# Math Homework Help

eNotes Homework Help is a way for educators to help students understand their school work. Our experts are here to answer your toughest academic questions! Once it’s posted to our site, your question could help thousands of other students.

• Math
The formula for the circumference of a circle is pi*d, where pi is a constant (pi approximately 3.1415926) and d is the diameter of the circle. Another formula for the circumference is C=2*pi*r...

Asked by enotes on via web

• Math
First of all, with any series problem, we must first decide if it is an arithmetic series or a geometric series. An arithmetic series is one that you can add or subtract to get from the first...

Asked by alicesmith on via web

• Math
The value of the function `f(x) = (x^2 - x - 2)/(x - 2)` is defined for all values of x other than x = 2. If we try to determine the value of f(x) at x = 2, we get `lim_(x->2) (x^2 - x - 2)/(x -...

Asked by tonys538 on via web

• Math
As per fundamental theorem of calculus, `F(t)=int_a^bf(t)dt=F(b)-F(a)` where F(t) is the antiderivative of f(t) and F'(t)=f(t), `d/dxint_a^bf(t)dt=b'F'(b)-a'F'(a)` Here a=0 so F(a)=0 , b=x^5...

Asked by vrwarrier on via web

• Math
First make a shorthand for the different types of articles to make the working clearer: p - no. of periodicals P n - no. of novels N w - no. of newspapers W (because N is already taken) h - no....

Asked by user6918912 on via web

• Math
Hello! The velocity is the derivative of the displacement function. Therefore we can find the displacement as the function of time by integrating the velocity function. For v(t) =` t^3 - 11t^2 +...

Asked by vrwarrier on via web

• Math
-xe^(-x) + e^(-x) = 0 Take the `e^(-x) ` as common ,we get => `e^(-x) [1-x]=0` => ` ((1-x)/(e^x)) =0` => `1-x =0` =>` x= 1`

Asked by enotes on via web

• Math
e^(-2x) - 2xe^(-2x) = 0 Taking the term e^(-2x) as common we get, => e^(-2x)[1-2x]=0 => ((1-2x)/(e^(2x))) =0 => (1-2x) = 0 * (e^(2x)) => 1-2x =0 => x = 1/2 = 0.500 the below...

Asked by enotes on via web

• Math
Given 2xln(x) + x = 0 => 2x ln(x) = -x cancelling x on both sides we get => 2 ln(x) = -1 => ln(x) = (-1/2) => x = e^(-1/2) = 0.6065 the graph of the equations 2x ln(x) +x =0 and y= 2x...

Asked by enotes on via web

• Math
`1-lnx=0 ` `lnx=1 ` Change to `log_e ` `log_(e)x=1 ` `e^1=x ` ` ` `x=2.719 `

Asked by enotes on via web

• Math
`1+lnx=0 ` `lnx=-1 ` Change to `log_(e) ` `log_(e)x=-1 ` `e^-1=x ` `x=0.368 `

Asked by enotes on via web

• Math
Given `2xln(1/x) - x=0` `x(2ln(1/x) -1)=0` so now, => `x= 0 or 2ln(1/x) - 1 =0` =>`2ln(1/x) - 1 =0` => `2ln(1/x) =1` => `ln(1/x) = 1/2` => `1/x = e^(1/2)` => `x = e^(-1/2) =...

Asked by enotes on via web

• Math
`lnx=7 ` Change to `log_e ` `log_(e)x=7 ` `e^7=x ` `x=1096.633 `

Asked by enotes on via web

• Math
Change to `log_e ` `log_(e)6x=2.1 ` `e^2.1=6x ` `x=e^2.1/6 ` `x=1.361 `

Asked by enotes on via web

• Math
Assume `log_10 ` `log_(10)3z=2 ` `10^2=3z ` `z=100/3 ` `z=33.333 `

Asked by enotes on via web

• Math
`ln5x=10/3 ` Change to `log_e ` `log_(e)5x=10/3 ` `e^(10/3)=5x ` `x=(e^(10/3))/5 ` `x=5.606 `

Asked by enotes on via web

• Math
Change to `log_e ` `log_(e)sqrt(x-8)=5 ` `e^5=sqrt(x-8) ` `(e^(5))^(2)=x-8` `e^10+8=x ` `x=22034.466 `

Asked by enotes on via web

• Math
`-6lnx=8 ` `lnx=-4/3 ` Change to `log_e ` `log_(e)x=-4/3 ` `e^(-4/3)=x ` `x=0.264 `

Asked by enotes on via web

• Math
`3lnx=10 ` `lnx=10/3 ` Change to `log_e ` `log_(e)x=10/3 ` `e^(10/3)=x ` `x=28.032 `

Asked by enotes on via web

• Math
`log_(3)0.5x=11/6 ` `3^(11/6)=0.5x ` Simplify, `x=14.988 `

Asked by enotes on via web

• Math
Assume `log_10 ` `log_(10)x-6=11/4 ` `10^(11/4)=x-6 ` `10^(11/4)+6=x ` Simplify, `x=568.341 `

Asked by enotes on via web

• Math
Use the properties of logarithms to condense the ln's `ln(x/(x+1))=2 ` Rewrite with log `log_(e)(x/(x+1))=2 ` `(x/(x+1))=e^2 ` `(x+1)/x=1/e^(2) ` `1+1/x=1/e^(2) ` `1/x=1/(e^(2))-1 `...

Asked by enotes on via web

• Math
Use properties of logarithms for the ln's `lnx(x+1)=1 ` `e=x(x+1) ` `e=x^2+x ` `x^2+x-e=0 ` Use the quadratic formula `x=1.223 ` and `x=-2.223 ` However, since you cannot take the log or ln of any...

Asked by enotes on via web

• Math
Use the properties of logarithms to condense the left side of the equation `ln(x+5)=ln((x-1)/(x+1)) ` Since you have 2 ln's, set the inner parts equal to each other `x+5=(x-1)/(x+1) ` Simplify,...

Asked by enotes on via web

• Math
Condense the equation using properties of logs `ln((x+1)/(x-2))=lnx ` Since there are ln's on both sides, set the inner parts equal to each other `(x+1)/(x-2)=x` Cross multiply and simplify,...

Asked by enotes on via web

• Math
Since you have logs on both sides, just set the inner parts equal to each other `3x+4=x-10 ` From here, it is simple algebra, just simplify, `x=-7 ` But this is not considered a real solution since...

Asked by enotes on via web

• Math
Since they are both `log_2 ` , rewrite it using properties of logs `log_(2)(x)(x+2)=log_2(x+6) ` Exponentiate both sides by 2 and solve for x `2^(log_(2)(x)(x+2))= 2^(log_2(x+6))` `x(x+2)=x+6 `...

Asked by enotes on via web

• Math
Note that `log_4(4)=1 ` `log_4x-log_4(x-1)=(1/2)log_4(4) ` Use log rules and condense `log_(4)(x/(x-1))=log_4(4^(1/2)) ` Exponentiate both sides by 4 and cancel logs: `x/(x-1)=sqrt4 ` `(x-1)/x=1/2...

Asked by enotes on via web

• Math
Given `log(8x) - log(1 + sqrt(x)) = 2` ---------------------(1) On simplification we get => As we know `log(a) - log(b) = log(a/b)` ` ` so , => ` log(8x) - log(1 + sqrt(x)) = 2` ` ` =>...

Asked by enotes on via web

• Math
Given `2(x^2)e^(2x) + 2xe^(2x) = 0` => `(e^(2x)) *(2(x^2) +2x)=0` =>`2x(e^(2x)) *(x +1) =0` =>` 2x(e^(2x)) = 0 or (x+1) =0` => as `(e^(2x))` cannot be zero so, `x = 0 ` and in `(x+1) =0...

Asked by enotes on via web

• Math
Given -(x^2)e^(-x) + 2xe^(-x) = 0 => e^(-x) [2x - x^2]=0 => (2x - x^2)/(e^(x) )=0 as (e^(x) ) cannot be zero so 2x- x^2 = 0 => x(2-x) =0 => x= 0 or x= 2 the graphs of the equations...

Asked by enotes on via web

• Math
Divide by 8 `3^(6-x)=5 ` Take the ln of both sides and bring down the exponent `(6-x)ln3=ln5 ` Simplify, `x=-ln5/ln3+6 ` `x=4.535 `

Asked by enotes on via web

• Math
Take the ln of both sides `lne^(3x)=ln12 ` Bring down the exponent `3xlne=ln12 ` Simplify, `x=0.828 `

Asked by enotes on via web

• Math
Divide both sides by 1000 `e^(-4x)=3/40 ` Take the ln of both sides and bring down the exponent `-4xlne=ln(3/40) ` Simplify, `x=0.648 `

Asked by enotes on via web

• Math
Subtract 7 from both sides `-2e^x=-2 ` Divide both sides by -2 `e^x=1 ` Take the ln of both sides and bring down the exponent `xlne = ln1 ` Simplify, x=0

Asked by enotes on via web

• Math
Add 14 to both sides `3e^x=25 ` Divide by 3 `e^x=25/3 ` Take the ln of both sides and bring down the exponent `xlne=ln(25/3) ` Simplify, `x=2.120 `

Asked by enotes on via web

• Math
Add 7 to both sides `6(2^(3x-1))=16 ` Divide by 6 `2^(3x-1)=8/3 ` Take the ln of both sides and bring down the exponent `(3x-1)ln2=ln(8/3) ` Simplify, `3x-1=ln(8/3)/ln2 ` `3x=ln(8/3)/(ln2)+1 `...

Asked by enotes on via web

• Math
Subtract 13 from both sides `8(4^(6-2x))=28 ` Divide by 8 `4^(6-2x)=7/2 ` Take the ln of both sides and bring down the exponent `(6-2x)ln4=ln(7/2) ` Simplify, `6-2x=ln(7/2)/ln4 ` `-2x=ln(7/2)/ln4-6...

Asked by enotes on via web

• Math
Given `2^x = 3^(x+1)` applying logarithmic on both sides we get `x*ln(2) = (x+1)ln(3)` `ln(2)/ln(3) = (x+1)/x` `ln(2)/ln(3) = 1+ 1/x` `ln(2)/ln(3) -1 = 1/x` `(ln(2) - ln(3))/ln(3) = 1/x` `x =...

Asked by enotes on via web

• Math
Take the ln of both sides `ln(2^(x+1))=ln(e^(1-x)) ` Move the exponents out in front `(x+1)ln2=(1-x)lne ` Multiply out using distributive property `xln2+ln2=lne-xlne` Gather the x terms on one...

Asked by enotes on via web

• Math
Given `4^x = 5^(x^2)` applying logarithims on both sides we get `ln(4^x) = ln(5^(x^2))` => `xln(4) = x^2 (ln(5))` => `ln(4) = x (ln(5))` `x = ln(4) / ln(5) = 0.8613` or `x= 0 `

Asked by enotes on via web

• Math
Given `3^(x^2) = 7^(6 - x)` applying logarithmics on both sides we get `ln(3^(x^2))=ln(7^(6 - x))` => `x^2 ln(3) = (6-x)ln(7)` => `x^2 ln(3) = 6*ln(7) - x* ln(7)` => `x^2 ln(3)+x*...

Asked by enotes on via web

• Math
`(e^x)^2-4e^x-5=0` Put `e^x=t.` `t^2-4t-5=0` `t^2-5t+t-5=0` `t(t-5)+1(t-5)=0` `(t-5)(t+1)=0` `t=5 or t=-1` `e^x = 5 and e^xgt0` Take ln on both sides, we get `x=ln5` `x=1.609`

Asked by enotes on via web

• Math
`(e^x)^2-5e^x+6=0` Put `e^x=t` `t^2-5t+6=0` `t^2-3t-2t+6=0` `t(t-3)-2(t-3)=0` `(t-2)(t-3)=0` `t=2 and t=3` `e^x=2 and e^x=3.` `x=ln2 and x=ln3.` `x=0.693 and x=1.099`

Asked by enotes on via web

• Math
`500=20(100-e^(x/2))` `100-e^(x/2)=25 ` `-e^(x/2)=-75 ` `e^(x/2)=75 ` Take the ln of both sides and bring down the exponent `(x/2)lne=ln75 ` Simplify, `x=8.635 `

Asked by enotes on via web

• Math
`400=350(1+e^(-x)) ` `1+e^(-x)=8/7 ` `e^-x=1/7 ` Take the ln of both sides `lne^(-x)=ln(1/7) ` Bring down the exponent `-xlne=ln(1/7) ` Simplify `x=1.946 `

Asked by enotes on via web

• Math
Take the ln of both sides `ln(1+0.065/365)^(365t)=ln4 ` Bring down the exponent `365tln(1+0.065/365)=ln4 ` Simply `t=21.330`

Asked by enotes on via web

• Math
Take the ln of both sides `ln(1.0083^(12t))=ln2 ` Bring down the exponent `12tln1.0083=ln2 ` Simplify `t=6.960 `

Asked by enotes on via web

• Math
Rewrite to `log_e` `log_(e)x=-3` `e^-3=x` `x=0.0498`

Asked by enotes on via web